2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2008
DOI: 10.1109/iembs.2008.4650367
|View full text |Cite
|
Sign up to set email alerts
|

Lean Six Sigma applied to a process innovation in a Mexican health institute's imaging department

Abstract: Delivery of services to a patient has to be given with an acceptable measure of quality that can be monitored through the patient's satisfaction. The objective of this work was to innovate processes eliminating waste and non value-added work in processes done at the Imaging Department in the National Institute of Respiratory Diseases (INER for its Spanish acronym) in Mexico City, to decrease the time a patient spends in a study and increase satisfaction. This innovation will be done using Lean Six Sigma tools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…(8) 1. The results obtained from indicator I 3 in the four measurement periods are shown in Table IV.…”
Section: E Learning Curves Of the X Ray Process A) Learning Curve Fomentioning
confidence: 99%
See 1 more Smart Citation
“…(8) 1. The results obtained from indicator I 3 in the four measurement periods are shown in Table IV.…”
Section: E Learning Curves Of the X Ray Process A) Learning Curve Fomentioning
confidence: 99%
“…The incorporation of this technology represented an important change in the way the service was provided, therefore it was necessary to analyze the general process in the ID and the sub-processes involved which are: Reception (RCP), X Ray (XR), Computed Tomography (CT), and Diagnosis (DX) [1]. Within the subprocesses there were identified the non value added activities and the opportunity areas; after these identifications a pilot program was generated which was consisted of the implementation of a series of innovations with two objectives: to make the processes more efficient, and use the ID's resources in a balanced way [2].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the application of the six sigma methodology in the health area has been very positive, in the United States for example, it was used in the Rapides Regional Center (Lousiana) to solve the problem of large waiting times; in the Women and Infants Hospital of Rhode Island, was used to standardize operational procedures in the movement of embryos [6]. In Mexico, it has been applied in the innovation of processes in the imaging department [7,8], as well as improving the process of health technology management [9].…”
Section: Introductionmentioning
confidence: 99%
“…. Porres.et.al [2] proposed that how LSS tools can be used to improve the process. Lean methodology was an exceptionally valuable tool to distinguish each Kaizen in every process, because it gives the fitting tackle to handle this sort of circumstances introduced at the Imaging Office.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This phase enhanced the confident in the user as at this level were identified and removed. A control plan was prepared and for the entire newly designed task verification [2] [3].…”
Section: E Controlmentioning
confidence: 99%